Malaria parasites release vesicle subpopulations with signatures of different destinations. (1st June 2022) - Abou Karam, Paula; Rosenhek‐Goldian, Irit; Ziv, Tamar; Ben Ami Pilo, Hila; Azuri, Ido; Rivkin, Anna; Kiper, Edo; Rotkopf, Ron; Cohen, Sidney R; Torrecilhas, Ana Claudia; Avinoam, Ori; Rojas, Alicia; et al.
Abstract: Malaria is the most serious mosquito‐borne parasitic disease, caused mainly by the intracellular parasite Plasmodium falciparum . The parasite invades human red blood cells and releases extracellular vesicles (EVs) to alter its host responses. It becomes clear that EVs are generally composed of sub‐populations. Seeking to identify EV subpopulations, we subject malaria‐derived EVs to size‐separation analysis, using asymmetric flow field‐flow fractionation. Multi‐technique analysis reveals surprising characteristics: we identify two distinct EV subpopulations differing in size and protein content. Small EVs are enriched in complement‐system proteins and large EVs in proteasome subunits. We then measure the membrane fusion abilities of each subpopulation with three types of host cellular membranes: plasma, late and early endosome. Remarkably, small EVs fuse to early endosome liposomes at significantly greater levels than large EVs. Atomic force microscope imaging combined with machine‐learning methods further emphasizes the difference in biophysical properties between the two subpopulations. These results shed light on the sophisticated mechanism by which malaria parasites utilize EV subpopulations as a communication tool to target different cellular destinations or host systems. Synopsis: Plasmodium falciparum invades human red blood cells and releases two extracellular vesicle subsets secreted by infected cells. These EV subpopulations harbor different protein cargo and have specific mechanical membrane properties, suggesting distinct host cell targets. Two distinct subsets of malaria‐derived EVs with different sizes are identified using asymmetric flow field‐flow fractionation. Small EVs are rich in complement system proteins, whereas large EVs contain 20S proteasome subunits. Small EVs are more efficient in fusing under endosomal conditions as compared to the large subset. The EV subpopulations possess distinct membrane mechanical properties, suggesting different lipid compositions. Abstract : Plasmodium falciparum invades human red blood cells and releases two extracellular vesicle subsets secreted by infected cells. These EV subpopulations harbor different protein cargo and have specific mechanical membrane properties, suggesting distinct host cell targets.